2009
DOI: 10.1364/ol.34.000455
|View full text |Cite
|
Sign up to set email alerts
|

Tunable pretilt angles based on nanoparticles-doped planar liquid-crystal cells

Abstract: The nanoparticles-induced vertical alignment technique was applied to generate variable liquid-crystal pretilt angles based on doping different concentrations of polyhedral oligomeric silsesquioxane (POSS) nanoparticles in the planar-aligned liquid crystal cells. Competition between the homogeneously aligned polyimide layer and POSS-induced spontaneous vertical alignment domain generated the variable pretilt angle. Experimental results demonstrated that the pretilt angle theta(p) is a function of the doped POS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…A voltage dependent colour tuning device has been fabricated using gold nanodot arrays formed from a sandwiched nematic LC cell [18]. The dispersion of nanoparticles (NP) in LCs (NP-doped LCs or LC/ NP composites) significantly influences LCD-relevant characteristics, such as, threshold voltage, pretilt angle, dielectric behaviour, and contrast ratio [19][20][21][22][23][24][25][26][27]. The Au-NP properties can be tuned with LCs which initiated changes in the localized surface plasmon resonances [28].…”
Section: Introductionmentioning
confidence: 99%
“…A voltage dependent colour tuning device has been fabricated using gold nanodot arrays formed from a sandwiched nematic LC cell [18]. The dispersion of nanoparticles (NP) in LCs (NP-doped LCs or LC/ NP composites) significantly influences LCD-relevant characteristics, such as, threshold voltage, pretilt angle, dielectric behaviour, and contrast ratio [19][20][21][22][23][24][25][26][27]. The Au-NP properties can be tuned with LCs which initiated changes in the localized surface plasmon resonances [28].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Recent investigations have demonstrated that polyhedral oligomeric silsesquioxane (POSS) materials can be used as additive materials for the vertical LC alignment system by doping the POSS materials to the LC and/or alignment layer. [15][16][17][18][19] It is not easy to reach a uniform distribution of the POSS in the LC and/or alignment layer to avoid POSS aggregation and/or agglomeration. The aggregated and/or agglomerated POSS into the LC and/or alignment layer can affect the aligning ability and E-O performance.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that an LC mixture with polyhedral oligomeric silsesquioxanes (POSS) exhibited vertical alignment without using an alignment layer [4], and the electro-optical characteristics were analysed [5]. The POSS-LC system was applied to ferroelectric LC cells [6], polymer-dispersed LCs [7], cholesteric LCs [8], mixtures with active reactive mesogens [9], a guest-host system [10] and planar alignment [11]. The advantages of the method are apparent; from an industrial point of view, it reduces the number of manufacturing steps, thereby decreasing the manufacturing cost.…”
Section: Introductionmentioning
confidence: 99%